Cardiac output response and peripheral oxygen extraction during exercise among symptomatic hypertrophic cardiomyopathy patients with and without left ventricular outflow tract obstruction. Issue 8 (21st January 2014) - Critoph, Christopher H; Patel, Vimal; Mist, Bryan; Elliott, Perry M
Abstract : Objective: Reduction of left ventricular outflow tract obstruction (LVOTO) often improves symptoms in hypertrophic cardiomyopathy (HCM), but the correlation between exercise performance and measured LVOT gradients is weak. We investigated the relationship between LVOTO and cardiorespiratory responses during exercise. Methods: The study cohort included 70 patients with HCM (32 with LVOTO, 55 male, age 47±13) attending a dedicated cardiomyopathy clinic and 28 normal volunteers. All underwent cardiopulmonary exercise testing with simultaneous non-invasive haemodynamic assessment using finger plethysmography. Main outcome measures were peak oxygen consumption, cardiac index and arteriovenous oxygen difference. Results: When compared with controls, patients had reduced peak exercise oxygen consumption (22.4±6.1 vs 34.7±7.7 mL/kg/min, p<0.0001) and cardiac index (5.5±1.9 vs 9.4±2.9 L/min/m 2, p<0.0001). At all workloads, stroke volume index (SVI) was lower and arteriovenous oxygen difference greater in patients. During all stages of exercise, LVOTO in patients was associated with failure to augment SVI and higher oxygen consumption; cardiac reserve (4.4±2.7 vs 6.3±3.6 L/min, p=0.025) and peak mean arterial pressure (104±16 vs 112±16 mm Hg, p=0.033) were lower. Multivariable predictors of cardiac output response were age (β: −0.11; CI −0.162 to −0.057; p<0.0001), peak LVOT gradient (β: −0.018; CI −0.034 to −0.002; p=0.031) and gender (β: −2.286; CI −0.162 to −0.577; p=0.01). Within the obstructive cohort, different patterns of SV response were elicited in patients with similar clinical features. Conclusions: Cardiac reserve is reduced in HCM because of failure of SV augmentation. LVOTO exacerbates this abnormal response, but haemodynamic responses vary significantly. Non-invasive exercise haemodynamic assessment may improve understanding of symptoms and help tailor therapy.